Perioperative Code Status Discussions: How Are We Doing?. Issue 6 (June 2021) - O'Leary, Sian; Pimentel, Marc Philip; Ford, Shauna; Vacanti, Joshua C.; Bleday, Ronald; Salmasian, Hojjat; Mendu, Mallika L.
Abstract : Approximately 15% of patients with a code status of do-not-resuscitate (DNR) or do-not-intubate (DNI) present for surgery. Despite professional guidelines requiring discussions with patients regarding perioperative resuscitation, it is unclear whether these recommendations are consistently followed. Our review of 158 patient encounters with established DNR/DNI code status found that code status discussions (CSDs) were documented only 70% of the time, and code status orders were inconsistently entered to reflect those discussions. We present solutions to improve CSD documentation, including refining perioperative workflows, simplifying code status choices, optimizing electronic health record order entry, and a supplementary consent form to facilitate code status review.